Extended cold storage of cultured hepatocytes impairs endocytic uptake during normothermic rewarming - Hovanyecz, P. (2013)
During hypothermic preservation of cells (0-4°C), metab¬olism is diminished and energy-dependent transport processes are arrested. The effect of hypothermic preservation of hepatocytes in endocytic transport following rewarming has not been previously reported. We evaluated the uptake of EGF (Epidermal Growth Factor) ligand conjugated to fluorescent Quantum Dots (QDs) probes in rat hepatocytes after 24 and 72 h cold storage in University of Wisconsin (UW) solution at 4°C. QDs uptake was visualized during rewarming to 37°C under air or, in a second approach, at the end of rewarming under 5% CO2. After 24 h in UW solution, QDs were internalized under both rewarming conditions similar to non-preserved hepatocytes and cells maintained a normal cytoskeleton distribution. However, in hepatocytes preserved 72 h none of the cells internalized QDs, which remained bound to the membranes. After rewarming, this group showed diminished actin staining while viability was maintained at ~70%. Our results present evidence that, hypothermic preservation for 72 h in UW solution at 4°C does not prevent EGFR (Epidermal Growth Factor Receptor) activation but irreversibly impairs endocytic uptake upon EGF stimulation; presumably due to actin cytoskeleton disassembling. Our approach can be applied on other membrane receptor systems and with other hypothermic preservation solutions to understand the effect of cooling in endocytic transport and to determine the optimal cold storage period.